2017
DOI: 10.1139/bcb-2016-0037
|View full text |Cite
|
Sign up to set email alerts
|

High concentration calcitriol induces endoplasmic reticulum stress related gene profile in breast cancer cells

Abstract: action for calcitriol will help development of novel treatment strategies. Since vitamin D exerts its cellular actions via binding to its receptor and by altering expressions of a set of genes, we aimed to evaluate the effect of calcitriol on transcriptomic profile of breast cancer cells. We previously demonstrated that calcitriol alters ER stress markers, therefore in this study we have focused on ERstress related genes to reveal calcitriols action on these genes in particular.We have treated breast cancer ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Recent studies have demonstrated that Nupr1 as a pro-survival gene while CHOP has pro-death functions associated with ER stress induced by calcitriol (Ozkaya et al, 2017). Nupr1 mediates its apoptotic effect through upregulation of the ER stress-related proteins ATF-4, CHOP and Trib3 (Carracedo et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that Nupr1 as a pro-survival gene while CHOP has pro-death functions associated with ER stress induced by calcitriol (Ozkaya et al, 2017). Nupr1 mediates its apoptotic effect through upregulation of the ER stress-related proteins ATF-4, CHOP and Trib3 (Carracedo et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…These factors include key canonical ER stress and UPR genes such as ATF4, DDIT3 (CHOP), PPP1R15A (GADD34), GADD45A (GADD45), XBP1, EIF2AK3 (PERK), and ATF3. Furthermore, IPA of NCI-H1703 cells treated with SSO Ex5 indicated that the top activated upstream pathways consist of gene networks that have been directly or indirectly linked to ER stress and the UPR [NUPR1 (32)(33)(34), z score = 9.34, P = 2.01 × 10 −11 ; MAP4K4 (35,36), z score = 5.04, P = 3.54 × 10 −10 ; ATF4 (37,38), z score = 3.82, P = 4.56 × 10 −10 ; CREB1 (39), z score = 3.06, P = 0.0174; EIF2AK3 (37,38), z score = 3.04, P = 2.54 × 10 − 7 ; CDKN1A (40), z score = 2.99, P = 0.00145] (Fig. 5B).…”
Section: Sso Ex5 Causes Endoplasmic Reticulum Stress and Activates Thementioning
confidence: 99%
“…PSMD4 is a well‐known proteasome ubiquitin receptor, and dysfunction in proteasome‐related protein degradation is tightly correlated with ERS . When misfolded proteins accumulate due to a damaged proteasome degradation system, the ERS level exceeds its own repair capability, and cell apoptosis is induced . We then attempted to reveal the possible correlation between PSMD4 and ERS.…”
Section: Discussionmentioning
confidence: 99%
“…32 When misfolded proteins accumulate due to a damaged proteasome degradation system, the ERS level exceeds its own repair capability, and cell apoptosis is induced. 33 We then attempted to reveal the possible correlation between PSMD4 and ERS. Western blot analysis demonstrated that silencing PSMD4 significantly increased the expression of GRP78, ATF6, and p-PERK, indicating an enhanced ERS response in EC cells.…”
Section: Discussionmentioning
confidence: 99%